Preparation And Characterization Of Polyimide/Inorganic Composite Films As Solid Dielectrics - Alias, Asliza (2012)
Considerable demand for solid thin-film dielectrics with high dielectric constants for use in the fabrication of capacitors has been observed. In this study, polyimide/inorganic composite films were prepared by incorporating different type of inorganic materials; Al2O3, BaTiO3, TiO2 and ZrO2, into polyimide (PI) derived from PMDA and ODA monomers via ultrasonication method. Chemical structure, morphology, dielectric and thermal properties were investigated by Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), LCR meter and thermal gravimetric analysis (TGA). FTIR spectra showed complete imidization, and all characteristic peaks of the imide groups are observed in PI/inorganic composite films. XRD diffractogram reveals that the PI/inorganic composite exhibits peaks similar to those of parent inorganic materials, indicating that the crystal structure of inorganic materials remain unchanged and stable after being doped into the PI matrix. SEM micrographs displays a uniform distribution of inorganic particles of Al2O3, BaTiO3 and TiO2 in the PI matrix by means of ultrasonication method and 3-aminopropyltrimethoxysilane coupling agent except for PI/ZrO2 composite. Meanwhile, the dielectric constants and dielectric losses of PI/inorganic composite films generally increase with the addition of inorganic content. The content of inorganic materials does not have significant effect on the degradation temperature of the PI/inorganic composites.